Implementasi Logika Fuzzy Mamdani pada Line Follower Robot dengan Fitur Obstacle Avoidance - Abraham Lincoln Pontoh; Muh. Firizki; Abdul Rahman (Universitas Multi Data Palembang, 2026)
This study presents the design and implementation of a Line Follower Robot equipped with an Obstacle Avoidance feature based on Mamdani Fuzzy Logic. The robot is designed to autonomously follow a predefined line while adapting its movement to avoid obstacles encountered along the path. Infrared sensors are used to detect the line position, while an ultrasonic sensor is utilized to measure the distance to obstacles. The decision-making process for controlling the direction and speed of the motors is handled using the Mamdani Fuzzy Logic method. System testing was conducted through experimental trials on various track conditions, including straight paths, turns, and branching tracks. Each condition was tested with 50 trials to evaluate system performance. The experimental results show that the robot achieved an average line-following success rate of 77%, with the highest performance on straight tracks and reduced performance on branching tracks due to increased track complexity. The obstacle avoidance system demonstrated effective detection and response with a reaction time of less than 1 second. These results indicate that the proposed system is capable of performing stable line-following and obstacle avoidance, and can serve as a basis for further development of autonomous mobile robots.